Development of an Ordering Application for Ayek Jerangan Shop in Tanjung Bunut Village Using the Waterfall Method - Dili Muhamad Padholi; Fajriyah; Riza Kartina (Yayasan Kita Menulis, 2026)
The development of information technology has improved efficiency in various sectors, including clean water distribution. In Tanjung Bunut Village, ayek jerangan (boiled or refillable drinking water) is a primary water source, but its ordering and distribution system remains conventional, causing irregular supply and fake orders. This study aims to design a web-based ordering application to improve efficiency, transparency, and accessibility for residents. The application is expected to help manage demand and distribution in a more structured manner and enhance service quality for the community.